Analisa Penerapan Akad dalam Pariwisata Syariah berdasarkan Fatwa MUI Dewan Syariah Nasional Nomor 108/DSN-MUI/X/2016 - Teguh Suripto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2019)
according to a study conducted by Master Card and Cresent Rating, in the Global Muslim Travel Index (GMTI), that in 2014 there were 108 million Muslim tourists representing 10 per cent of the entire tourism industry. Therefore it is very important that Yogyakarta starts to prepare sharia tourism packages or halal tourism packages. Sharia tourism can be prepared by referring to or referring to the MUI fatwa that has been issued as a guideline for the community to understand the understanding and management of halal tourism or sharia tourism. This study will use a descriptive methodology, which describes the object through observation and literature search that is relevant to the object of the study. The results of the study concluded that Islam provides guidance or guidance to its followers in travelling in accordance with Islamic values. In accordance with tourism, appropriate agreements have been determined, as stated in the MUI fatwa on sharia tourism, including ijarah, ju'alah, and wakalah bil ujrah. The development of DIY tourism needs to involve all tourism stakeholders including scholar